2013
DOI: 10.1038/hdy.2012.124
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific clines support incipient speciation in a common European mammal

Abstract: Hybrid zones provide excellent opportunities to study processes and mechanisms underlying reproductive isolation and speciation. Here we investigated sex-specific clines of molecular markers in hybrid zones of morphologically cryptic yet genetically highly-diverged evolutionary lineages of the European common vole (Microtus arvalis). We analyzed the position and width of four secondary contact zones along three independent transects in the region of the Alps using maternally (mitochondrial DNA) and paternally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…In the present study, we confirmed that the Western and the Basal lineages co-occur in the eastern part of the Swiss Alps, although individuals from the Basal lineage were rare and restricted to a single location. All of these processes were observed in bank voles or closely-related species (Le Galliard et al, 2012;Sutter, Beysard & Heckel, 2013;Boraty nski et al, 2014) and, with the data available, it is difficult to disentangle them in the present study. Indeed, when forcing STRUCTURE to assign populations to two genetic groups based on microsatellite data, the Basal population was not separated from the Western populations.…”
Section: Discussionmentioning
confidence: 72%
“…In the present study, we confirmed that the Western and the Basal lineages co-occur in the eastern part of the Swiss Alps, although individuals from the Basal lineage were rare and restricted to a single location. All of these processes were observed in bank voles or closely-related species (Le Galliard et al, 2012;Sutter, Beysard & Heckel, 2013;Boraty nski et al, 2014) and, with the data available, it is difficult to disentangle them in the present study. Indeed, when forcing STRUCTURE to assign populations to two genetic groups based on microsatellite data, the Basal population was not separated from the Western populations.…”
Section: Discussionmentioning
confidence: 72%
“…, Sutter et al. ; Beysard and Heckel ). Along the same line, the occurrence of sharp clines for both X and Y chromosomes relative to autosomes (such as found in rabbits and mice) cannot result from sex differences in migration only, but rather point to DM incompatibilities involving both X and Y chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although demographic processes can result in skewed ratios (Van Belleghem et al, 2018), modelling of strictly neutral divergence suggests that Φ ST Z:Autosomal ratios > 5 could be generated only if the effective population size of Z-linked loci is 10%-20% the effective size for autosomal loci (as compared to the standard expectation of 75%), which is unlikely in ducks (Lavretsky et al, 2015). Although sex chromosomes are often found to harbour outliers thought to be important in speciation (Dhami, Joseph, Roshier, & Peters, 2016;Ellegren et al, 2012;Lavretsky et al, 2015;Martin et al, 2013;Minvielle, Ito, Inoue-Murayama, Mizutani, & Wakasugi, 2000;Phadnis & Orr, 2009;Pryke, 2010;Ruegg, Anderson, Boone, Pouls, & Smith, 2014;Saether et al, 2007;Sutter, Beysard, & Heckel, 2013), caution is warranted in making conclusions about the relative importance of loci with different modes of inheritance based on data representing a relatively small proportion of the genome. In particular, it is important to consider that higher linkage disequilibrium in sex chromosomes relative to autosomes (Bergero & Charlesworth, 2009) increases the probability of capturing outlier loci when using reduced representation methods (e.g., ddRAD-seq; Samuk et al, 2017).…”
Section: Outlier Distribution and Genomic Diversity In The Nw "Mallmentioning
confidence: 99%